Surgery of the anus, rectum & colon - Keighley, M.R.B; Williams, Norman S. 1947- (Elsevier Saunders, 2008)
The third edition continues to redefine the field, with its comprehensive coverage of common and rare colorectal conditions, advances in the molecular biology and genetics of colorectal diseases, new laparoscopic techniques, and more. Contributions from international experts on specialized topics and 400 new illustrations ensure that the extensive text is not only current and authoritative, but easy to understand. No other book provides the expertise of a world-class editorial team with the cutting-edge knowledge you need to master colorectal surgery.